2005
DOI: 10.1007/s00592-005-0196-9
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic control and educational status in children with type 1 diabetes: effects of a summer camp and intensive insulin treatment

Abstract: Our aim was to evaluate prospectively, in our diabetic patients, the impacts of a summer camp and intensive insulin treatment (IIT) on both metabolic control and disease-related educational level. Twenty-five patients participated in a 7-day-long summer camp. Before the camp, all patients were on therapy with short-acting human insulin (SAI) and intermediate-acting insulin (IAI) twice daily. On arrival, their insulin therapy regimen was changed by IIT including either SAI or rapid-acting insulin analogue (RAI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
7

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 9 publications
3
24
0
7
Order By: Relevance
“…This was probably related to the increase in physical activity and the healthier dietary measures adapted to the nutritional needs of each camper while maintaining the pre-camp insulin doses. To reduce the frequency of hypoglycemia during camp, organizers usually monitor and reduce the usual insulin doses of campers by 10–30 % upon arrival [5, 10, 15, 18]. The reduction in insulin doses alongside an appropriate dietary plan permitted the significant reduction in the frequency of hypoglycemia, which went down from 1.3 episodes per camper per day at the beginning to 0.5 at the end of the camp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was probably related to the increase in physical activity and the healthier dietary measures adapted to the nutritional needs of each camper while maintaining the pre-camp insulin doses. To reduce the frequency of hypoglycemia during camp, organizers usually monitor and reduce the usual insulin doses of campers by 10–30 % upon arrival [5, 10, 15, 18]. The reduction in insulin doses alongside an appropriate dietary plan permitted the significant reduction in the frequency of hypoglycemia, which went down from 1.3 episodes per camper per day at the beginning to 0.5 at the end of the camp.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was small, although comparable to that of the majority of quality prospective studies [5, 10, 15, 17]. The initial number of campers was limited to ensure better monitoring and also to avoid accidents.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of knowledge in health education must not be ignored, because increased knowledge is the first step toward health behavior modification; thus, many studies have incorporated knowledge building into their intervention programs 9,22,25,26. However, a systematic review reported that the effect of educational intervention on diabetes knowledge was unclear, with 12 of 30 studies reporting a significant impact 27.…”
Section: Discussionmentioning
confidence: 99%
“…Obserwacje poczynione na stosunkowo krót-kich 5-7-dniowych turnusach wakacyjnych podkreślają, poza walorami edukacyjnymi i poprawą samokontroli [13][14][15], także wzrost u dzieci i nastolatków akceptacji choroby i wzrost adaptacji do codziennego życia [16,17].…”
Section: Dyskusjaunclassified